Evaluation of antioxidant properties of selected cyanobacterial strains for potential use as natural antioxidants - Anjali, S; Kamakshi; Devendra, K (Plant Science Today, 2025)
Cyanobacteria are recognized for their antioxidant properties; however, comparative analyses of strain-specific antioxidant capacity are scarce, particularly among isolates from agricultural soils. In this study, seven cyanobacterial strains (Nostoc sp., Anabaena sp., Westiellopsis sp., Oscillatoria sp., Tolypothrix sp., Calothrix sp., Phormidium sp.), isolated from rice fields of Uttar Pradesh, India, were evaluated for their antioxidant capacity. Ferric reducing antioxidant power (FRAP) assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and 2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation decolorization assay were used to analyze antioxidant activity. Trolox (μmol trolox g-1) was used to standardise the antioxidant capacity. Anabaena sp. showed the highest antioxidant activity among all the strains tested in all three assays, with values of 9.12 ± 0.05 μmol trolox g-1 ABTS assay, 8.96 ± 0.03 μmol trolox g-1 FRAP assay and 8.93 ± 0.03 μmol trolox g-1 DPPH assay. Tolyprothrix sp. showed the lowest antioxidant activity in all assays, with values of 5.02 ± 0.05 μmol trolox g-1 ABTS assay, 4.12 ± 0.03 μmol trolox g-1 FRAP assay and 4.01 ± 0.02 μmol trolox g-1 DPPH assay. These results imply that the species and assay technique significantly influence the antioxidant capacity of cyanobacterial strains. The study emphasises the importance of selecting appropriate assay techniques when assessing the antioxidant potential of cyanobacteria. The observed diversity underscores the necessity of using standardised protocols to evaluate and compare the antioxidant characteristics of various strains. Further research is recommended to explore potential applications in medicines and nutraceuticals and to investigate the underlying metabolic processes responsible for the observed antioxidant effects. This comparative investigation highlights the significance of selecting suitable cyanobacterial strains for the extraction of antioxidant compounds. By identifying high-activity strains, researchers can enhance the application of natural antioxidants in food preservation, cosmetic formulations and therapeutics.